Estratégias competitivas e o poder de negociação dos compradores: estudo de caso em uma indústria de bebidas - Cunha, José César Silva (2006)
This dissertation presents, through a case study, in an industry of soft drinks section, located in the state of Rio Grande do Sul, a model for formulation of competitive strategies addressed to powerful buyers of the industries of soft drinks section, that makes possible to the managers, the search for a sustained business growth, to improve the competitive position and to reduce the vulnerability to their exercise of the power, through the analysis of the structural position and atmosphere of a branch of activity buyers’, with the identification of the current strategies, tendencies and opportunities, competitive positioning choice, internal processes identification, organizational competences and establishment of a plan of businesses with activities and marketing strategies, that seek to assure the generation of value for the customer. At the end of the work, we concluded: 1) more than to remove individual advantage in the relationship, buyers and suppliers should feel counts they make part of a chain of supplies of products or services directed to the consumer; 2) the business is profitable when the value that the company creates is superior at the cost of the acting of the activities of value; 3) the importance of analyzing the structural and sectorial position, when choosing the competitive strategy and the elaboration of the plan of businesses; 4) when elaborating a business plan, identifying all of the relevant internal processes, and the organizational competences that generate values for the customer and, the most important, 5) an organization is only effective when there is understanding of the relationship among strategy, their practices and their competences.